Wpływ zaburzeń mowy u dzieci sześcio- i siedmioletnich na naukę czytania i pisania - Zając, Ewelina (Teoria i praktyka logopedyczna. Wybrane zagadnienia, 2018)
The aim of this article was to investigate how and which speech disorders affect learning to read and write in six-year-old children preparing to start schooling and in first-graders. The study involved 36 first-grade students and 27 six-year-old children attending reception class. The speech therapy diagnosis showed that almost 62% of the students tested had particular speech disorders. Among the diagnosed disorders, the most common were defects in articulation due to peripheral reasons. The group of sounds not articulated correctly were the dented (humming and hissing), the [r] and the voiced sounds. The causes of speech defects are of great importance for the relationship between reading and writing difficulties and speech defects. The research shows that a significant proportion of students have impaired phonemic hearing, which affects the occurrence of articulation defects, and thus errors in reading and writing. Also, a clear relationship can be observed between the delayed speech development and specific reading disorders, because writing difficulties are the result of delayed speech development, especially the delayed acquisition of the language system.